Strengthening HOTS Thinking in Islamic Education in the Era Of Society 5.0 - Talabudin Umkabu (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2022)
Islamic education is currently faced with the challenges of the Society 5.0 era, which demands success in developing higher order thinking skills (HOTS) in students. This study aims to understand the concept of HOTS in Islamic education, analyze the challenges of Islamic education in developing HOTS in the Society 5.0 era, and provide solutions to strengthen the development of HOTS in Islamic education. The research method used is a literature study and descriptive analysis. The results showed that HOTS is a more complex thinking ability that requires analytical, creative and critical abilities. The challenges of Islamic education in developing HOTS in the Society 5.0 era are the lack of teachers who are trained in developing HOTS, the lack of appropriate use of technology in learning, and the lack of support from parents and society. Solutions to strengthen HOTS development in Islamic education include teacher training in developing HOTS, appropriate use of technology in learning, and involving parents and the community in supporting student HOTS development. In order to strengthen HOTS development in Islamic education, collaborative and synergistic efforts are needed between educational institutions, government, community, and other stakeholders.